SIMULATION-GAME APPROACH AS A BASIS TECHNOLOGIES OF PREPARATION OF FUTURE TEACHERS TO CREATIVE ACTIVITY - L.V. Kondrashova (Academy of Cognitive and Natural Sciences, 2001)
This article deals with playing technologies in students' preparing to their professional activity. The author shows the advantage of imitative-playing teaching in activization of training work and development o f creative abilities of teachers to come.